Nonthermal radio continuum emission from young nearby stars - Launhardt, Ralf; Loinard, Laurent; Dzib, Sergio A.; Forbrich, Jan; Bower, Geoffrey C.; Henning, Thomas; Mioduszewski, Amy J.; Reffert, Sabine (The astrophysical journal, 2022)
Young and magnetically active low-mass stars often exhibit nonthermal coronal radio emission owing to the gyration of electrons in their magnetized chromospheres. This emission is easily detectable at centimeter wavelengths with the current sensitivity of large radio interferometers like the Very Large Array (VLA). With the aim of identifying nearby stars adequate for future accurate radio astrometric monitoring using very long baseline interferometry (VLBI), we have used the VLA in its B configuration to search for radio emission at ν ≃ 6 GHz (λ ≃ 5 cm) toward a sample of 170 nearby (<130 pc), mostly young (5-500 Myr) stars of spectral types between F4 and M2. At our mean 3σ detection limit of ≃50 μJy, we identify 31 young stars with coronal radio emission (an 18% system detection rate) and more than 600 background (most likely extragalactic) sources. Among the targeted stars, we find a significant decline of the detection rate with age from 56% ± 20% for stars with ages ≤10 Myr to 10% ± 3% for stars with ages 100-200 Myr. No star older than 200 Myr was detected. The detection rate also declines with T eff from 36% ± 10% for stars with T eff < 4000 K to 13% ± 3% for earlier spectral types with T eff > 5000 K. The binarity fraction among the radio-bright stars is at least twice as high as among the radio-quiet stars. The radio-bright nearby young stars identified here provide an interesting sample for future astrometric studies using VLBI arrays aimed at searching for hitherto-unknown tight binary components or even exoplanets.
Gesehen am 11.08.2022